Modern manuscripts - Van Hulle, D (Oxford University Press, 2019)
The study of modern manuscripts to examine writing processes is termed “genetic criticism.” A current trend that is sometimes overdramatized as “the archival turn” is a result of renewed interest in this discipline, which has a long tradition situated at the intersection between modern book history, bibliography, textual criticism, and scholarly editing. Handwritten documents are called “modern” manuscripts to distinguish them from medieval or even older manuscripts. Whereas most extant medieval manuscripts are scribal copies and fit into a context of textual circulation and dissemination, modern manuscripts are usually autographs for private use. Traditionally, the watershed between older and “modern” manuscripts is situated around the middle of the 18th century, coinciding with the rise of the so-called Geniezeit, the Sturm und Drang (Storm and Stress) period in which the notion of “genius” became fashionable. Authors such as Goethe carefully preserved their manuscripts. This new interest in authors’ manuscripts can be part of the “genius” ideology: since a draft was regarded as the trace of a thought process, a manuscript was the tangible evidence of capital-G “Genius” at work. But this division between modern and older manuscripts needs to be nuanced, for there are of course autograph manuscripts with cancellations and revisions from earlier periods, which are equally interesting for manuscript research. Genetic criticism studies the dynamics of creative processes, discerning a difference between the part of the genesis that takes place in the author’s private environment and the continuation of that genesis after the work has become public. But the genesis is often not a linear development “before” and “after” publication; rather, it can be conceptualized by means of a triangular model. The three corners of that model are endogenesis (the “inside” of a writing process, the writing of drafts), exogenesis (the relation to external sources of inspiration), and epigenesis (the continuation of the genesis and revision after publication). At any point in the genesis there is the possibility that exogenetic material may color the endo- or the epigenesis. In the digital age, archival literary documents are no longer coterminous with a material object. But that does not mean the end of genetic criticism. On the contrary, an exciting future lies ahead. Born-digital works require new methods of analysis, including digital forensics, computer-assisted collation, and new forms of distant reading. The challenge is to connect to methods of digital text analysis by finding ways to enable macroanalysis across versions.